Koncepcje teorii ryzyka - Sołtysiak, Mirosław; Suraj-Sołtysiak, Magdalena (Risk as a Factor of Company's Operating, 2006)
Issues concerning risk and uncertainty's occurrence in entrepreneur ship are presented in the article The first part includes both survey and comparison of selected theories on risk and uncertainty. The latter part encompasses the core idea of risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 153-159